PENERAPAN MANAJEMEN MEREK PADA USAHA KECIL DAN MENENGAH (UKM) - Rahab . (Jurnal Bisnis dan Ekonomi, 2009)
Mostly problems are faced by Small Medium Enterprises (SMEs) thatrelated to marketing aspect. Role of brand very important to SMEs in order its productis recognized easily by consumers. Implementation of brand management in SMEs willassist the brand recognition to their customers. This paper seeks to offer concept ofcreating brand awareness, brand management models, brand development model inSMEs. Implementation of effectiveness brand management consider about type andstrategy of business at each SMEs.The paper suggests that word by mouth strategy effectively to increasebrand awareness. The primary factor determining successful of brand management atSMEs is commitment of owners to focus in recognizing their brands. Owners havedouble roles in brand management is as director or manager that give intensivelyattention to brand management and as entrepreneurs who to be personification ofproduct’s brand.Key words: Brand management, Brand awareness, Small Medium Enterprises.